DIFFERENTIATED APPROACH TO THE PRESERVATION OF THE ROOTS OF TEETH AND THEIR USE IN DENTAL PROSTHETICS - S.V. Irkha (Ukrainian Medical Stomatological Academy, 2016)
Actuality of theme. The problem of the maximum preservation of decayed teeth is the practical importance for the prevention of deformities dentition and alveolar process atrophy. In addition, the preservation of decayed teeth will prevent their removal from the consequences. One of the main causes of tooth extraction is a problem associated with drug treatment and root canal filling, especially heavily traversed, and in the case of kistohranulom and other pathological processes in the tissues surrounding the tooth that requires a balanced approach to their preparation for dental prosthetics. Therefore, to be considered appropriate for further clinical and laboratory research to develop sustainable ways to prepare the roots of teeth to orthopedic treatment and improvement known to improve the efficiency of orthopedic treatment of patients with complete or partial defect coronal tooth. Materials and methods. In accordance with the purpose we examined 203 patients, aged 24 to 56 years, who applied to the Department of Prosthetic Dentistry "Kyiv Medical University UAFM" for orthopedic care. Preliminary examination showed the need to prepare the roots of teeth for dental prosthesis manufacture of orthopedic designs these patients. They used a complex scheme of examination, the result of which were found indications for the manufacture of pin tumbler designs. Of these, 143 patients (64 men and 79 women), the clinical situation in the mouth which allow use pin designs, were taken for treatment. All patients made a complete endodontic intervention on standard protocols, in addition to the basic groups of observations, which at the finish root canal treatment elektrofulhuration using the method developed by us in cooperation with prof. S.I.Doroshenko et al. In some patients conducted microbiological research content root canal to action electrosurgical treatment. The ability to use the roots of teeth when the complete destruction of coronal and destruction in the zone of bifurcation can extend the indications for use of fixed constructions of dentures in patients with dentition defects. To select orthopedic design for our proposed way to compensate for the defect in the crown shattered bifurcation in the clinic we conducted mechanics and mathematical modeling of stress-strain state of the periodontal tooth under chewing load after orthopedic treatment. Conclusion. The results of the microbiological tests can conclude that the use of a variety of additional assets that contribute to the elimination of persistent bacterial infection in root canals and periapical their part, can increase the efficacy of treatment of teeth and their roots. Based on mechanics and mathematical modeling of stress-strain state periodontal and the calculations it was found that the angles chewing effort of more than 15° for preservation of teeth that were orthopedic treatment, it is necessary to limit the component force of chewing, which aims to vestibular-lingual direction. The use of our suggested benign ways of preserving the roots of teeth with dental prosthesis as studies have shown, can keep the roots of decayed teeth and use them as a support for various designs of dentures.